2020
DOI: 10.3390/ijms21072541
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Proteomic Analysis of Watermelon Fruits in Response to Cucumber green mottle mosaic virus Infection

Abstract: Cucumber green mottle mosaic virus (CGMMV) is an important viral pathogen on cucurbit plants worldwide, which can cause severe fruit decay symptoms on infected watermelon (usually called “watermelon blood flesh”). However, the molecular mechanism of this disease has not been well understood. In this study, we employed the isobaric tags for relative and absolute quantitation (iTRAQ) technique to analyze the proteomic profiles of watermelon fruits in response to CGMMV infection. A total of 595 differentially acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…In terms of plant-virus interactions, plants have evolved immune systems that recognize the presence of viruses and initiate the expression of effective defense response factors. Recently, two studies have reported on transcriptome and proteomic profiles of CGMMV-infected and mock-inoculated watermelon leaves or fruit [ 19 , 29 ]. We compared them with our RNA-seq data and found that the number of DEGs identified in previous RNA-seq data (1641 DEGs) was similar to our study (1855 DEGs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of plant-virus interactions, plants have evolved immune systems that recognize the presence of viruses and initiate the expression of effective defense response factors. Recently, two studies have reported on transcriptome and proteomic profiles of CGMMV-infected and mock-inoculated watermelon leaves or fruit [ 19 , 29 ]. We compared them with our RNA-seq data and found that the number of DEGs identified in previous RNA-seq data (1641 DEGs) was similar to our study (1855 DEGs).…”
Section: Discussionmentioning
confidence: 99%
“…We compared them with our RNA-seq data and found that the number of DEGs identified in previous RNA-seq data (1641 DEGs) was similar to our study (1855 DEGs). Most of the DEGs or differentially accumulated proteins (DAPs) in the three studies were induced by CGMMV infection and functional analyses indicated they enriched in the pathways involved in stress response, photosynthesis, secondary metabolism, and so on [ 19 , 29 ]. These results further validated the common pathways in watermelon involved in CGMMV response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPS proteins are linked to protein synthesis. RPS14 has been described to be up regulated in watermelon when challenged with cucumber green mottle mosaic virus [50]. It is known that a repression of protein synthesis is usually associated with the selective translation of mRNA that encode proteins that are crucial for stress recovery and thus cell survival.…”
Section: Several Daps Are Significantly Repressed At Both Time Pointsmentioning
confidence: 99%
“…As powerful tools, proteomic technologies can also discern global protein expression changes during plant responses to biotic and abiotic stresses at the cellular and molecular levels. The Isobaric Tags for Relative and Absolute Quantitation (iTRAQ) technology has been used in proteomics studies due to its high efficiency and accuracy in identifying differentially expressed proteins (DEPs) [ 32 , 33 , 34 ]. This technology is used to analyze proteomics in response to different biotic or abiotic stresses, including heat stress [ 35 ], salt stress [ 36 ], drought tolerance [ 37 ], rice response to Magnaporthe oryzae [ 38 ], defense response in cotton triggered by Rhizoctonia solani [ 39 ], and Arabidopsis response to Verticillium dahliae [ 40 ].…”
Section: Introductionmentioning
confidence: 99%